2005
DOI: 10.1128/aac.49.12.4920-4927.2005
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Meropenem Minimum Concentration/MIC Ratio To Suppress In Vitro Resistance of Pseudomonas aeruginosa

Abstract: Suppression of resistance in a dense Pseudomonas aeruginosa population has previously been shown with optimized quinolone exposures. However, the relevance to ␤-lactams is unknown. We investigated the bactericidal activity of meropenem and its propensity to suppress P. aeruginosa resistance in an in vitro hollow-fiber infection model (HFIM). Two isogenic strains of P. aeruginosa (wild type and an AmpC stably derepressed mutant [MIC ‫؍‬ 1 mg/liter]) were used. An HFIM inoculated with approximately 1 ؋ 10 8 CFU/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
156
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(167 citation statements)
references
References 30 publications
10
156
0
1
Order By: Relevance
“…Tam et al showed that for meropenem, the PD target needed to suppress the emergence of resistance in P. aeruginosa was a C min :MIC ratio of 1.7. 38 Further study is still needed in the area of resistance suppression but the current data suggest that obtaining the PK/PD target against the range of MIC encountered clinically is not likely with conventional b-lactam dosing and will most likely require more intensive regimens administered over extended periods of time. 38 …”
Section: Additional Pharmacokinetic and Pharmacodynamic Considerationsmentioning
confidence: 99%
“…Tam et al showed that for meropenem, the PD target needed to suppress the emergence of resistance in P. aeruginosa was a C min :MIC ratio of 1.7. 38 Further study is still needed in the area of resistance suppression but the current data suggest that obtaining the PK/PD target against the range of MIC encountered clinically is not likely with conventional b-lactam dosing and will most likely require more intensive regimens administered over extended periods of time. 38 …”
Section: Additional Pharmacokinetic and Pharmacodynamic Considerationsmentioning
confidence: 99%
“…This is commonly referred to as the free drug time above the MIC (fT Ͼ MIC). The level of exposure required for a bactericidal effect also varies depending on the ␤-lactam class, with carbapenem, penicillin, and cephalosporin antibiotics, in general, requiring approximately 40%, 50%, and 50 to 70% fT Ͼ MIC, respectively, for a bactericidal effect (27); however, some reports have demonstrated a benefit to providing greater exposures (i.e., 100% fT Ͼ MIC) (24). As a result of this knowledge, numerous approaches have been made to maximize the fT Ͼ MIC by altering antibiotic dosage regimens in an effort to improve patient outcomes and lower antibiotic-related costs.…”
mentioning
confidence: 99%
“…This intrinsic tolerance of ␤-lactams likely accounts for the fact that when P. aeruginosa infections are treated, optimal microbiological outcomes occur when ␤-lactam concentrations are maintained at 4 to 6.6 times the MIC throughout the majority of the dosing period (13). Furthermore, ␤-lactam tolerance by P. aeruginosa can lead to the emergence of spontaneous ␤-lactam-resistant strains (12,14). Thus, ␤-lactam tolerance provides significant challenges for clinicians when treating P. aeruginosa infections.…”
mentioning
confidence: 99%